The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2967/jnumed.107.048207
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effective Use of 18F-FDG PET in the Presurgical Evaluation of Medically Refractory Focal Epilepsy

Abstract: This study applied decision tree analysis to evaluate the sensitivity, specificity, and cost-effectiveness of clinical algorithms that incorporate 18 F-FDG PET. Methods: A cohort of 176 patients was studied. The localization rate, accuracy, therapeutic impact on the presurgical decision-making process, and correlation with the postsurgical outcome were assessed for the tests commonly performed for seizure localization. Decision tree sensitivity analysis compared 3 imaging strategies with a baseline strategy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 30 publications
1
39
1
Order By: Relevance
“…The O'Brien et al study 78 was the only published study found in the review process that was considered to be in line with the scope of this assessment. The study was conducted from the viewpoint of an Australian health-care provider.…”
Section: Conclusion Of Review Of Existing Cost-effectiveness Evidencementioning
confidence: 60%
See 4 more Smart Citations
“…The O'Brien et al study 78 was the only published study found in the review process that was considered to be in line with the scope of this assessment. The study was conducted from the viewpoint of an Australian health-care provider.…”
Section: Conclusion Of Review Of Existing Cost-effectiveness Evidencementioning
confidence: 60%
“…78 The following section provides an overview of this paper and assesses its relevance to the scope of this technology assessment.…”
Section: Methods Of Systematic Review Of Existing Cost-effectiveness mentioning
confidence: 99%
See 3 more Smart Citations